Respuesta :
Hi there!
X-INTERCEPT
To find the x-intercept of a function, we need to substitute y = 0 into the equation and then solve for x.
[tex]2x - 6y = 24[/tex]
Substitute y = 0
[tex]2x - 6(0) = 24[/tex]
Multiply
[tex]2x - 0 = 24[/tex]
We can now remove the 0.
[tex]2x = 24[/tex]
And finally divide by 2.
[tex]x = 12[/tex]
Since we've plugged in y = 0, we already have the complete coordinate of the x-intercept, which is (12, 0).
Y-INTERCEPT
To find the y-intercept of a function, we need to substitute x = 0 into the equation and then solve for y.
[tex]2x - 6y = 24[/tex]
Substitute x = 0
[tex]2(0) - 6y = 24[/tex]
Multiply.
[tex]0 - 6 y = 24[/tex]
Remove the 0.
[tex] - 6y = 24[/tex]
And finally divide by-6.
[tex]y = - 4[/tex]
Since we've plugged in x = 0, we already have the complete coordinate of the y-intercept, which is (0, -4).
Hence, the answer is: "The x-intercept is (12, 0); the y-intercept is (0, −4)."
~ Hope this helps you!
X-INTERCEPT
To find the x-intercept of a function, we need to substitute y = 0 into the equation and then solve for x.
[tex]2x - 6y = 24[/tex]
Substitute y = 0
[tex]2x - 6(0) = 24[/tex]
Multiply
[tex]2x - 0 = 24[/tex]
We can now remove the 0.
[tex]2x = 24[/tex]
And finally divide by 2.
[tex]x = 12[/tex]
Since we've plugged in y = 0, we already have the complete coordinate of the x-intercept, which is (12, 0).
Y-INTERCEPT
To find the y-intercept of a function, we need to substitute x = 0 into the equation and then solve for y.
[tex]2x - 6y = 24[/tex]
Substitute x = 0
[tex]2(0) - 6y = 24[/tex]
Multiply.
[tex]0 - 6 y = 24[/tex]
Remove the 0.
[tex] - 6y = 24[/tex]
And finally divide by-6.
[tex]y = - 4[/tex]
Since we've plugged in x = 0, we already have the complete coordinate of the y-intercept, which is (0, -4).
Hence, the answer is: "The x-intercept is (12, 0); the y-intercept is (0, −4)."
~ Hope this helps you!